Exploring the Translator’s Methods in Literary Translation: Strategies, Challenges and Considerations - Abdulxamidova Xanifaxon Odiljon qizi, Abdulazizov Dovudbek (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
Literary translation is a complex and nuanced process that requires translators to navigate linguistic, cultural, and stylistic differences to convey the essence of a work from one language to another. This article delves into the methods employed by translators in literary translation, highlighting key strategies, challenges, and considerations. From maintaining fidelity to the original text to capturing the author’s voice and style, translators play a crucial role in bridging cultural divides and bringing diverse literary traditions to a global audience.